Ethical Ideologies of Senior Australian Managers: An Empirical Study - Fernando, Mario (Journal of business ethics, 2008)
Forsyth’s (1980) Ethics Position Questionnaire and Hunt et al.’s (1989) Corporate Ethical Value Questionnaire are used to examine the ethical ideologies of senior managers from organizations listed in the Australian Stock Exchange. The results indicate how corporate ethical values, religion, gender, and age are related to the idealism and relativism of senior Australian managers. After discussing the results, limitations of the study are offered. Finally, managerial implications are provided and recommendations for future research are given.